Considerations on the Update of the Risk Assessment Document During the Pandemic State by COVID-19 in Italy - Cirrincione, Luigi; Rapisarda, Venerando; Ledda, Caterina; Vitale, Ermanno; Provenzano, Rosanna; Cannizzaro, Emanuele (Frontiers in Public Health, 2021)
Immediately after the outbreak of the SARS-CoV-2 epidemic (which had risen to the level of a pandemic according to the World Health Organization), the question arose whether or not to update the risk assessment, which, as required by Legislative Decree 81/2008, with the consequent updating of the prevention measures. In light of these forecasts, we asked ourselves whether the risk of coronavirus infection should be taken into account by the employer by updating the risk assessment or not. An in-depth analysis of current legislation has led to the conclusion that the biological risk from SARS-CoV-2 is to be considered specific only in health-related activities, in other activities it can be considered exclusively generic or generic aggravated. The Risk Assessment Document can therefore only be integrated.